Brothers three - Oskison, John M. (John Milton), 1874-1947 (The Macmillan Company, 1935)
Francis Odell came to Indian Territory in the 1870s and married a part Indian woman. Together, they took to farming and prospered, building a heritage for their three sons. None of his sons, however, wish to follow in his footsteps. Bud wants to be a mechanic or storekeeper, Bunny is a born cattleman, and Mister wants to be a writer, and live in New York City.